Características socioeconómicas de la población pesquera del barrio Venecia del Mar de Puerto Bolívar - Morocho Mejia, Jaime Gabriel (2013)
This research is the study of the socioeconomic situation of artisanal fishermen in the "Venice of the Sea" neighborhood Puerto Bolivar. In this the problems affecting the work of the traditional fishing neighborhood is analyzed and makes a proposal to improve the quality of life of fishermen in this sector